Определение магнитного квадруполя технического объекта статическим контурным измерительным преобразователем - Ивлева, Любовь Федоровна; Пелевин, Дмитрий Евгеньевич (НТУ "ХПИ", 2003)
Рассчитаны параметры статического контурного первичного измерительного преобразователя, позволяющего измерять тессеральные компоненты квадрупольного магнитного момента технического объекта.

The parameters of a static planimetric primary measuring transducer permitting to measure tesseral components of a quadrupole magnetic moment in a technical object are calculated.
Definition of a magnetic quadrupole in technical object by measuring with a static planimetric transducer
Keywords: измерительный преобразователь; тессеральные компоненты; квадрупольный магнитный момент; магнитное поле; technical object; quadrupole magnetic moment; tesseral component; measuring transducer